sendo f(x)=3x-x^2 e g(x)=x+1, então (f o g) (x) ( função composta) é:
Soluções para a tarefa
Respondido por
0
Boa tarde!
![f(x) = 3x - {x}^{2} \\ g(x) = x + 1 \\ \\ (fog)(x) = 3(x + 1) - {(x + 1)}^{2} \\ (fog)(x) = 3x + 3 - ( {x}^{2} + 2x + 1) \\ (fog)(x) = - {x}^{2} + x + 2 f(x) = 3x - {x}^{2} \\ g(x) = x + 1 \\ \\ (fog)(x) = 3(x + 1) - {(x + 1)}^{2} \\ (fog)(x) = 3x + 3 - ( {x}^{2} + 2x + 1) \\ (fog)(x) = - {x}^{2} + x + 2](https://tex.z-dn.net/?f=f%28x%29+%3D+3x+-++%7Bx%7D%5E%7B2%7D++%5C%5C+g%28x%29+%3D+x+%2B+1+%5C%5C++%5C%5C+%28fog%29%28x%29+%3D+3%28x+%2B+1%29+-++%7B%28x+%2B+1%29%7D%5E%7B2%7D++%5C%5C+%28fog%29%28x%29+%3D+3x+%2B+3+-+%28+%7Bx%7D%5E%7B2%7D++%2B+2x++%2B+1%29++%5C%5C+%28fog%29%28x%29+%3D++-++%7Bx%7D%5E%7B2%7D++%2B+x+%2B+2)
Perguntas interessantes
História,
10 meses atrás
Matemática,
10 meses atrás
História,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás